Napoleon - Ellis, Geoffrey James (London Longman, 1997)
A biography of the military genius, who in 1804 crowned himself Emperor of the French and established a vast European empire.
Includes bibliographical references and index.
Keywords: Napoleon -- Emperor of the French -- 1769-1821 -- Juvenile literature; Napoleon -- Emperor of the French -- 1769-1821.; Kings, queens, rulers, etc; France -- History, Military -- Juvenile literature. -- 1789-1815.; France -- Kings and rulers -- Juvenile literature. -- Biography; France -- Politics and government -- Juvenile literature. -- 1789-1815.